PKM Kelompok Kerajinan Pengolahan Sampah Plastik Di Kecamatan Kota Tengah Kota Gorontalo - Syamsul Syamsul; Syaiful Pakaya; Moh. Muhrim (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
The plastic waste processing handicraft group is a group consisting of housewives who process waste or plastic waste into a handicraft product that has economic added value for group members. During its formation the group only produced handicraft products from used plastic bottles such as flower pots and wall hangings. The problems experienced by this group start from the production process, business management, and marketing. The results of the implementation through the community partnership program (CPM) the companion team provided solutions related to problems faced by partners, namely providing materials and training partners who have started using plastic plastic waste bags as handicraft products in the form of handbags, flower garlands, and flower fitting, as well as the availability of partners raw material providers that support production. Providing material as well as how to make financial reports, the result is that partners already have production and sales records, and know turnover. Partners are also given organizational training, as a result group members have already done work based on the given job. Providing material and training on how to market products, the result is that partners already have online marketing media in the form of Facebook and Instagram fanpages. Marketing partner networking, where partners already have product marketing partners, namely in stalls and stalls in the market.